2019
DOI: 10.1200/jco.2019.37.27_suppl.151
|View full text |Cite
|
Sign up to set email alerts
|

Identifying levels of financial toxicity and unmet needs in cancer patients receiving financial assistance: Exploring trends in populations lacking adequate resources to overcome healthcare barriers.

Abstract: 151 Background: The inability to afford healthcare has a widespread effect on cancer patients, notably impacting treatment decisions and outcomes. Patients receiving financial assistance to offset medication costs still face challenges overcoming cost of care barriers. This study investigated sources of concern and financial stress among racial groups and identified solutions to address patients’ needs beyond medication-related costs. Methods: This cross-sectional study utilized secondary survey data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Participants reported they may not make the recommendations they would like to because of financial concerns or health literacy. Other studies have found that financial concerns such as insurance, out of pocket expenses, and transportation are major barriers reported by patients with cancer (Barris et al, 2019; Lin et al, 2008). It has also been established that financial barriers can decrease patient adherence to treatment, which was also reported to be a barrier by our participants (Barris et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reported they may not make the recommendations they would like to because of financial concerns or health literacy. Other studies have found that financial concerns such as insurance, out of pocket expenses, and transportation are major barriers reported by patients with cancer (Barris et al, 2019; Lin et al, 2008). It has also been established that financial barriers can decrease patient adherence to treatment, which was also reported to be a barrier by our participants (Barris et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that financial concerns such as insurance, out of pocket expenses, and transportation are major barriers reported by patients with cancer (Barris et al, 2019; Lin et al, 2008). It has also been established that financial barriers can decrease patient adherence to treatment, which was also reported to be a barrier by our participants (Barris et al, 2019). Another study found that uptake of recommended colorectal cancer screening was lower among those with lower health literacy, which indicates health literacy can also impact patient adherence to treatment (Kobayashi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%